Case report: secondary pleural hydatidosis - Ozyurtkan, Mehmet O?uzhan; Koçyi?it, Semih; Cakmak, Muharrem; Ozsoy, Ibrahim Ethem; Balci, Akin Eraslan (My University, 2009)
Hydatid cyst has a predilection to locate in liver, lungs, and brain. Intrathoracic extrapulmonary locations are generally the mediastinum, pleura, pericardium and chest wall. Pleural involvement usually follows the rupture of a pulmonary or hepatic cyst inside the pleural space causing secondary pleural hydatidosis. Radiological investigations of a patient suffering from cough and dyspnea revealed multiple cysts located in the posterior lower right hemithorax, and implanted in the diaphragmatic pleura and parietal pleura lining the chest wall. He had undergone two hepatic hydatid cystectomy operations. These multiple cysts were removed by thoracotomy. The possibility of secondary pleural dissemination should be considered in patients with lobulated cystic masses as well as a previous hepatic cystic hydatid disease.
Keywords: Aged; Albendazole; Anticestodal Agents; Echinococcosis; Humans; Magnetic Resonance Imaging; Male; Pleural Diseases; Recurrence; Tomography, X-Ray Computed; albendazole; anticestodal agent; aged; article; case report; computer assisted tomography; echinococcosis; human; male; nuclear magnetic resonance imaging; parasitology; pleura disease; recurrent disease